Chromatin deregulation in cancer - Armstrong, Scott A.,Ed; Henikoff, Steve,Ed; Vakoc, Christopher R.,Ed (Cold spring harbor laboratory press, 2017)
"The machinery that controls how DNA is packaged and genes are activated plays an important role in cancer. This book examines the functions of components of this machinery, how they can be dysregulated, and the prospects for targeting them therapeutically. Highlights include: - PRC2 polycomb complex - Therapy- Lysine demethylase inhibitors - Epigenetic mechanisms of therapy resistance and tumor heterogeneity - Long non-coding RNA"--